Accuracy of Nutrient Intake Values From Four Popular Nutrition Tracking Apps. (7th June 2021) - Evenson, Alexa; Berens, Betsy
Abstract: Objectives: To assess the accuracy of nutrient intake values from four popular nutrition tracking apps including, MyFitnessPal, MyNetDiary, SparkPeople, and Cronometer, compared to ESHA-Food Processor. Methods: One-day food records were obtained from 30 students in an introductory nutrition course. After demonstrating inter-rater reliability (ICC > 0.90), food records were entered by two researchers into ESHA-Food Processor, MyFitnessPal (MFP), My Net Diary (MND), Spark People(SP), and Cronometer (CR) apps to determine nutrient intake values. Wilcoxon sign rank test and Spearman correlation coefficients were used to analyze the data comparing the apps to ESHA. Results: Energy intake values were significantly lower for MFP ( P  = 0.002), MND ( P  = 0.002), SP ( P  = 0.003); but not for CR ( P  > 0.05) when compared to ESHA. Fat intake values were significantly lower for MFP ( P  = 0.003), MND ( P  = 0.003), SP ( P  = 0.006), but not CR ( P  = 0.249). Carbohydrate intake values were significantly lower for MFP ( P  = 0.005), MND ( P  = 0.002), SP ( P  = 0.004), and CR ( P  = 0.026) when compared to ESHA. There were no differences in protein or fiber intake values between any of the apps compared to ESHA ( P  > .05). Sodium intake values were lower for MFP ( P  < 0.001), MND ( P  = 0.014), and CR ( P  = 0.019) compared to ESHA, while SP did not estimate sodium intake. Conclusions: A majority of the nutrition tracking apps calculated lower energy values and lower intake values of multiple nutrients compared to ESHA-Food processor. Users of the popular nutrition tracking apps, including consumers, educators, and researchers, should be aware of the significant differences in nutrient intake calculations as energy and many nutrients could be under-reported. Funding Sources: No funding was provided.